Complicated multiple pregnancy referral, treatment and outcomes at the NSW Fetal Therapy Centre. Issue 3 (August 2014) - Tetstall, Emma; Shand, Antonia W; Welsh, Alec W; Chen, Katie Q; Henry, Amanda
Abstract: Objectives : To determine the indications for referral, sonographic workload, diagnoses and outcomes of women with a multiple pregnancy referred to the New South Wales Fetal Therapy Centre (NSW FTC). Methods : Retrospective cohort study of twin and higher order multiple (HOM) pregnancies referred to the NSW FTC at the Royal Hospital for Women (RHW) Department of Maternal Fetal Medicine (MFM), Sydney from January 2007 to December 2009. Results : There were 176 twin pregnancies (138 monochorionic diamniotic, 29 dichorionic diamniotic and nine monoamniotic), and 26 HOMs referred (23 triplet and three quadruplet pregnancies). Indications for referral were: twin to twin transfusion syndrome (TTTS) 103 women, fetal anomaly 31 women, intrauterine growth restriction (IUGR) 12 women, serial surveillance of twins or HOM 37 women, and fetal reduction of HOM (nine women). In 80.2% the pathological referral diagnosis was confirmed. The average number of ultrasounds was five (range 1–24), with 90 women (45%) receiving invasive therapy. Thirty‐five percent (71) of referrals were from outside Sydney, including eight interstate and 11 overseas referrals. Two‐thirds of out of area referrals were able to return to their referral hospital for birth: 95 women (47%) delivered at RHW. Conclusion : TTTS was the most common reason for referral, with a high concordance between referral and initial diagnosis. RHW accepted a large number of out of area referrals, in keeping with its role as the NSW FTC. Twin and HOM pregnancy referrals represent a significant workload for the 5 department, with many women also requiring invasive therapy.